"Perrotta Psychotherapeutic Protocol for Disorders of the Neurotic Area" (PPP-DNA): Proposal of protocol, profiles and clinical applications. Research - Giulio Perrotta (Open Journal of Trauma - Peertechz Publications, 2021)
Purpose: This research addresses the topic of anxiety, phobic and obsessive disorders. In this research, the theme is addressed to the psychopathological investigation of personalities, according to the PICI-2TA model (Perrotta Integrative Clinical Interviews, version 2-TA), the PAD-Q (Perrotta Affective Dependency Questionnaire), the PSM (Perrotta Sexual Matrix), the PDM-Q (Perrotta Defence Mechanisms Questionnaire) and the PHEM model (Perrotta Human Emotions Model), in order to design a direct and functional psychotherapeutic protocol to manage the psychopathological process in the shortest time possible, according to the principles of efficiency, effectiveness and economy, trying to reduce the symptomatology until the total regression by the fifth-tenth session. Methods: Clinical interview and administration of the PICI-2, the PAD-Q, the PSM, and the PDM-Q.  Results: In the male group, aged 18-36 years, there were 8 people, of whom 6 (75%) reacted to the total resolution of the neurotic symptomatology described between the fifth and ninth sessions, while only 2 (25%) said they felt their neurotic symptoms had subsided. In the male group, aged 37-54 years, there are 5 people, of whom 4 (80%) reacted to the total resolution of neurotic symptomatology described between the fifth and ninth sessions. In the male group, aged 55-72 years, there were 6 people, of whom 4 (66.6%) reacted to the total resolution of neurotic symptoms described between the ninth and tenth sessions. In the female group, aged 18-36 years, there were 22 people, of whom 18 (82%) reacted to the total resolution of neurotic symptoms described between the fifth and ninth sessions. In the female group, aged 37-54 years, there were 13 people, of whom 9 (69.2%) reacted to the total resolution of neurotic symptoms described between the fifth and ninth session. In the female group, aged 55-72 years, there were 11 people, of whom 8 (72.7%) reacted to the total resolution of neurotic symptoms described between the fifth and ninth sessions. Conclusions: The research showed that the PPP-DNA protocol, for neurotic disorders, was effective in the total population sample for 74.36%, for the fractionated male population sample for 73.86% and for the fractionated female population sample for 74.86%, with resistance to change identified in adverse conditions of family, environmental, socio-cultural and temporal type (of duration of neurotic symptomatology), however able to promote an attenuation of the symptomatology suffered by at least 50%.